Incorporating resilience and cost in ecological restoration strategies at landscape scale - Stefanes, Maurício; Ochoa-Quintero, Jose Manuel; De Oliveira Roque, Fabio; Moreira Sugai, Larissa Sayuri [UNESP]; Tambosi, Leandro Reverberi; Lourival, Reinaldo; Laurance, Susan (Resilience Alliance, 2016)
The restoration of deforested or degraded areas can contribute to biodiversity conservation and global resilience given the current and projected impacts of climate change. In recent years, a robust array of ecological restoration frameworks have been generated to address restoration challenges at large scales in different ecosystems around the world. Unfortunately, the costs associated with restoration at such scales greatly challenges the implementation of such frameworks. We used landscape ecology principles with multicriteria optimization of landscape resilience and agricultural productivity as a way to mitigate the trade-offs between production and restoration. We used the Cerrado biome in Mato Grosso do Sul State, Brazil, as a case study to apply our framework. We compared three scenarios: minimal legal compliance (MLC); selection by ecological resilience (SER); and selection by restoration cost (SRC). Our results show that increasing the restoration target from MLC (25%) to SER (30%) means moving from 968,316 to 1592 million hectares, which can represent a huge opportunity cost for agricultural lands. However, because costs and resilience are not homogeneously distributed throughout landscapes, we can select areas of intermediate ecological resilience and low cost, for the same restoration area target. This process can reduce potential conflicts and make restoration a more viable process. Our results also reveal some areas that can be particularly important for reconciling agriculture and landscape restoration. Those areas combined high and intermediate resilience and an above average profitability. This could mean that increasing restoration in this area could be very expensive, assuming that our proxy roughly represents the restoration implementation cost. However, there is another important message here, that some areas can be productive at the same time that they maintain levels of resilience above the legal compliance, which facilitates win-win scenarios in human-dominated landscapes.
Keywords: Decision-making tool; Ecological resilience; Fragmentation; Opportunity cost; Prioritization restoration; Restoration costs; Trade-off analysis